Pengaruh Penambahan Laurat dan Glisin terhadap Nilai Warna dan Kadar Sitrinin Angkak - Susana Ristiarini; Muhammad Nur Cahyanto; Jaka Widada; Endang Sutriswati Rahayu (Faculty of Agricultural Technology, Universitas Gadjah Mada, Yogyakarta, Indonesia, 2018)
Angkak, commonly used for food colorant and flavor enhancers in oriental cuisine, is the result of fermentation by Monascus purpureus on steamed rice. In addition to producing pigments Monascus purpureus, Angkak also produces mycotoxins, citrinin, which is hepato-nephrotoxic. Biosynthesis of pigment and citrinin is following a polyketide synthase pathway and then subdivides to form pigment or citrinin. Fatty acids and amino acids are known to be the precursors of red pigment formers in their biosynthetic pathways. The purpose of this research was to know the effect of addition of lauric fatty acid and amino acid glycine on steamed rice substrate to the color characteristic and citrinin level by M. purpureus JK9A. The amount of fatty acid and glycine was respectively 0.5% and 1% (w/w). Fermentation was carried out for 14 days and every two days the solids content of fermented products, pH, number of cells, colors, pigments dissolved in water were measured. The level of citrinin was tested at the end of the fermentation period (14th day). There was no significant difference between treatments for the solids content of about 23 ̶ 29% and the number of cells 6.32 ̶ 6.56 logCFU/g. While the pH value, color and water-soluble pigments were significantly different between treatment and control. The ˚hue values of glycine and combination of lauric-glycine were 16.11 and 15.33, respectively, lower than controls (22.76). The highest A500nm/A400nm ratio was in the combination treatment of lauric-glycine and the lowest levels of citrinin also in the treatment of lauric-glycine combination. This study noticed that the addition of lauric or glycine and its combination in rice media for Monascus purpureus JK9A fermentation proved to increase the biosynthesis of red pigment (46.34%) and decrease citrinin level up to 49.97%.